Gold nanoparticles for treatment of experimental burns - Volkova, N.; Yukhta, M.; Goltsev, A. (Nanosystems, Nanomaterials, Nanotechnologies. 2019;,17(4): 597–608, 2019)
At present, among many types of nanoparticles, gold nanoparticles (AuNPs) are the most promising in biology and medicine due to the wide range of valuable chemical and physical properties. The goal of the present study is to investigate a possibility of cell-free application of the AuNPs in methylcellulose gel (MG) to treat full-thickness experimental burns in rats. Thermal burns of grade 3 are modelled in rats. The next day after the injury, the animals were randomly divided into three groups: control group without a treatment; research group 1 with application of MG; research group 2 with application of both MG and AuNPs (6 g/ml). As shown, the superficial application of MG containing AuNPs improves the general status of animals, accelerates the wound-healing process by increasing cell proliferation and subsequent regulation of collagen synthesis/degradation. The results concerning the effect of AuNPs application in regenerative processes in burns provide some preonditions for the following advanced nanomedical-technology developments. _____________________________________________________________________________________________ Нині, серед багатьох типів наночастинок, наночастинки золота (AuNPs) є найбільш перспективними в біології та медицині завдяки широкому спектру цінних хемічних і фізичних властивостей. Метою цього дослідження було вивчення можливости безклітинного використання AuNPs в метилцелюлозному ґелі (MҐ) для лікування глибоких експериментальних опіків. Термічні опіки 3-го ступеня моделювали на щурах. На наступний день після травми тварини випадковим чином були розділені на три групи: контрольна група без лікування; експериментальна група 1 із нанесенням МҐ; експериментальна група 2 із застосуванням MҐ й AuNPs (6 мкг/мл). Було показано, що поверхневе використання MҐ, що містить AuNPs, поліпшувало загальний стан тварин, пришвидшувало процес загоювання ран за рахунок збільшення проліферації клітин і подальшої реґуляції синтези/деґрадації колаґену. Одержані тут результати впливу AuNPs на реґенеративні процеси при опіках да- ють деякі передумови для подальшого розвитку наномедичних технологій. ____________________________________________________________________________________________________ Ныне, среди многих типов наночастиц, наночастицы золота (AuNPs) являются наиболее перспективными в биологии и медицине благодаря широкому спектру ценных химических и физических свойств. Целью настоящего исследования было изучение возможности бесклеточного использования AuNPs в метилцеллюлозном геле (МГ) для лечения глубоких экспериментальных ожогов. Термические ожоги 3-й степени моделировали на крысах. На следующий день после травмы животные случайным образом были разделены на три группы: контрольная группа без лечения; экспериментальная группа 1 с нанесением МГ; экспериментальная группа 2 с применением МГ и AuNPs (6 мкг/мл). Было показано, что поверхностное использование МГ, содержащего AuNPs, улучшало общее состояние животных, ускоряло процесс заживления ран за счёт увеличения пролиферации клеток и последующей регуляции синтеза/деградации коллагена. Полученные тут результаты влияния AuNPs на регенеративные процессы при ожогах дают некоторые предпосылки для дальнейшего развития наномедицинских технологий.
Volkova N., Yukhta M., Goltsev A. Gold nanoparticles for treatment of experimental burns Nanosystems, Nanomaterials, Nanotechnologies. 2019;,17(4): 597–608
Keywords: gold nanoparticles; methylcellulose gel; experimental burns; regeneration; наночастинки золота; метилцелюлозний ґель; експериментальні опіки; реґенерація; наночастицы золота; метилцеллюлозный гель; экспериментальные ожоги; регенерация